Weber's 'use and abuse' of Calvin's Doctrine of Predestination. Issue 3 (2nd September 2018) - Adair-Toteff, Christopher
ABSTRACT: In the Protestant Ethic and the Spirit of Capitalism, Max Weber demonstrates his mastery in many different fields. However, Weber acknowledged that he was no expert in theology and he admitted that he had relied on a number of theological sources for his treatment of Calvin. Unfortunately, an examination of his sources reveals that Weber was highly selective. He not only chose what he wanted to use; he also dismissed those theologians whose ideas did not seem to fit his interpretation. Weber did not provide us with an account of Calvin's Doctrine of Predestination as it was, but he gave us one as he wanted it to be.